Normative values for carotid intima media thickness and its progression: Are they transferrable outside of their cohort of origin? - Liao, X.; Norata, Giuseppe; Polak, J.; Stehouwer, C.; Catapano, A.; Rundek, T.; Ezhov, M.; Sander, D.; Thompson, S.; Lorenz, M.; Balakhonova, T.; Safarova, M.; et al. (Sage Publications, 2016)
© 2016 European Society of Cardiology. Background The clinical use of carotid intima media thickness (cIMT) requires normal values, which may be subject to variation of geographical factors, ethnicity or measurement details. The influence of these factors has rarely been studied. The aim of this study was to determine whether normative cIMT values and their association with event risk are generalizable across populations. Design Meta-analysis of individual participant data. Method From 22 general population cohorts from Europe, North America and Asia we selected subjects free of cardiovascular disease. Percentiles of cIMT and cIMT progression were assessed separately for every cohort. Cox proportional hazards models for vascular events were used to estimate hazard ratios for cIMT in each cohort. The estimates were pooled across Europe, North America and Asia, with random effects meta-analysis. The influence of geography, ethnicity and ultrasound protocols on cIMT values and on the hazard ratios was examined by meta-regression. Results Geographical factors, ethnicity and the ultrasound protocol had influence neither on the percentiles of cIMT and its progression, nor on the hazard ratios of cIMT for vascular events. Heterogeneity for percentiles of cIMT and cIMT progression was too large to create meaningful normative values. Conclusions The distribution of cIMT values is too heterogeneous to define universal or regional population reference values. CIMT values vary widely between different studies regardless of ethnicity, geographic location and ultrasound protocol. Prediction of vascular events with cIMT values was more consistent across all cohorts, ethnicities and regions.